A large pericardial cyst mimicking a unilateral pleural effusion: A case report. Issue 15 (14th April 2023) - Li, Minfang; Yang, Chunfeng; Li, Jinshuai; Jia, Dan; Wang, Yaqiong; Xie, Wei; Wang, Jinlin
Abstract : Rationale: Pericardial cysts are a rare benign disorder with a variable clinical presentation depending on their size and location. The diagnosis of pericardial cysts is usually based on imaging examinations. The definitive treatment is surgical resection. Patient concern: A 36-year-old woman presented with progressive left-sided chest pain and exertional dyspnea, with symptoms resembling pleural effusion. Diagnoses: The patient was diagnosed with a pericardial cyst based on imaging and video-assisted thoracoscopic surgery (VATS). Intervention: VATS was performed. Outcomes: The patient's symptoms improved after successful removal of the pericardial cyst. Follow-up chest computed tomography exhibited no evidence of recurrence. Lessons: Clinicians should include pericardial cysts in the differential diagnosis of pseudopleural effusion. VATS is a feasible and safe method to treat symptomatic and large pericardial cysts.